Asymmetric toroidal eddy currents (ATEC) to explain sideways forces at JET. (9th August 2016) - Roccella, R.; Roccella, M.; Riccardo, V.; Chiocchio, S.
Abstract: During some JET vertical displacement events (VDEs) plasma current and position are found to be toroidally asymmetric. When asymmetries lock, the vessel has been observed to move horizontally, consequently strong horizontal forces are expected following plasma asymmetries, whether locked or rotating. The cause of horizontal forces is, as already identified in previous works, the asymmetric circulation of current in the structures. The physics mechanism responsible for these asymmetric currents is instead an open issue and it is the object of the present analysis. In particular it will be shown that the asymmetry is not due to a direct exchange of current between plasma and structure (as in the case of halo currents) but to asymmetric conductive paths which arise, in the structures, when the plasma column asymmetrically wets the wall. Simulations of this phenomenon using finite element (FE) models have been conducted to reproduce the JET observation during locked and rotating asymmetric VDEs. Estimated sideways force, asymmetry ( I p asym ) and normalized asymmetry ( A p asym ) of plasma current, vertical position at different toroidal locations during the disruption and halo current asymmetry have been compared with measurements done at JET during upward AVDEs. The substantial match between experiments and simulations confirms the soundness of the assumptions. Furthermore, the same physical model applied to downward VDEs shows that divertor support and coils, together with the geometry of the limiting surfaces, considerably lessen asymmetric loads as experienced at JET after installing those components.